Routine Histopathological Evaluation of Tonsillitis Specimens before Tonsillectomy: Analysis of Clinician Perspective and Opted Practices - Nighat Arif, Beenish Kanwal, Muhammad Haris Hassan, Sehar Naseem, Poonam Singla, Asiya Mussaddiq (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To analyses the clinicians perspective on routine histopathological evaluation of tonsillitis specimens before tonsillectomy. Study Design: Cross sectional study. Place and Duration of Study: ENT Department, Islamic International Medical College, Rawalpindi from 1st July 2021 to 30th June 2022. Methodology: One hundred clinicians from both genders were enrolled and 14 questions based proforma was generated. All questions were answered in yes, no or not applicable domains. The survey was software designed and uploaded on a software post data receive. The sample size for collecting data was taken as hundred ENT clinicians were actively practicing and performing surgical procedures. Results: The mean age of the clinicians was 41.3±5.6 years. Majority of the clinicians had an experience of 10-20 years. 32% of the clinicians only sent adult samples for hisptopathoocal asseseemtn while only 5% of the peditric cases were sent for same before tonsillectomy while there were 33% such clinicians who sent it foradults as well as pediatric cases. Conclusion: There are more clinicians who sent adult tonsillitis specimens for histopathological assessment than pediatric cases individually while 33% are such clinicians who sent both adults and pediatrics samples for histopathological evaluation before tonsillectomy. Keywords: Evaluation, Tonsillectomy, Histopathological assessment